Nature's marvels endowed in gaseous molecules I: Carbon monoxide and its physiological and therapeutic roles - Xiaoxiao Yang; Wen Lu; Christopher P. Hopper; Bowen Ke; Binghe Wang (Elsevier, 2021)
Nature has endowed gaseous molecules such as O2, CO2, CO, NO, H2S, and N2 with critical and diverse roles in sustaining life, from supplying energy needed to power life and building blocks for life's physical structure to mediating and coordinating cellular functions. In this article, we give a brief introduction of the complex functions of the various gaseous molecules in life and then focus on carbon monoxide as a specific example of an endogenously produced signaling molecule to highlight the importance of this class of molecules. The past twenty years have seen much progress in understanding CO's mechanism(s) of action and pharmacological effects as well as in developing delivery methods for easy administration. One remarkable trait of CO is its pleiotropic effects that have few parallels, except perhaps its sister gaseous signaling molecules such as nitric oxide and hydrogen sulfide. This review will delve into the sophistication of CO-mediated signaling as well as its validated pharmacological functions and possible therapeutic applications.